The Volatility–Variability Hypotheses Testing and Hedging Effectiveness of Precious Metals for the Indonesian and Malaysian Capital Markets - Robiyanto Robiyanto; Sugeng Wahyudi; Irene Rini Demi Pangestuti (Gadjah Mada International Journal of Business, 2017)
This study evaluates the use of futures contracts for precious metals to hedge against stock market risks and their hedging effectiveness on the Indonesian Stock Exchange (IDX) and the Kuala Lumpur Stock Exchange (KLSE). This study found that gold was the most effective hedging instrument, since it produced the highest hedging effectiveness both on the IDX and the KLSE among the other precious metals. None of the hedged portfolios had a higher Sharpe’s ratio than the unhedged one on the IDX; however, all the hedged portfolios on the KLSE had a higher Sharpe’s ratio than the unhedged ones. Almost all the hedged portfolios could produce a higher Treynor’s ratio than the unhedged portfolios, both on the IDX and the KLSE. In general, this study concluded that studying some precious metals could reduce the investment risk, which was shown through the variance produced by the smaller portfolios, while gold can improve the risk-adjusted performance.